2014
DOI: 10.1186/1471-2458-14-144
|View full text |Cite
|
Sign up to set email alerts
|

Changes in exposure to ‘life stressors’ in the Aboriginal and Torres Strait Islander population, 2002 to 2008

Abstract: BackgroundThe Negative Life Events Scale (NLES) has been included in nationally representative surveys of the Indigenous and Australian population since 2002 as a measure of exposure to a range of ‘life stressors’. There has been limited reporting or analysis of estimates of the NLES from these surveys. This paper reports changes in exposure to stressors from 2002 to 2008 for the Indigenous population, and examines inter-relationships between eleven NLES items. Data for the 2006 Australian population is also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…While we were surprised to find that those who believe smoking reduces their stress were no less motivated to quit, our outcomes were limited to quit attempts and not the success of such attempts. Connections between smoking and stress, or psychological reactions to stress, would benefit from further study using measures shown to be sensitive to the multiple life stressors and high levels of psychological distress experienced by Aboriginal and Torres Strait Islander peoples 32 , 33 . Exploration of supports and strategies that enable successful quitting in the presence of these stressors is also indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we were surprised to find that those who believe smoking reduces their stress were no less motivated to quit, our outcomes were limited to quit attempts and not the success of such attempts. Connections between smoking and stress, or psychological reactions to stress, would benefit from further study using measures shown to be sensitive to the multiple life stressors and high levels of psychological distress experienced by Aboriginal and Torres Strait Islander peoples 32 , 33 . Exploration of supports and strategies that enable successful quitting in the presence of these stressors is also indicated.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 While we were surprised to find that those who believe smoking reduces their stress were no less motivated to quit, our outcomes were limited to quit attempts and not the success of such attempts. Connections between smoking and stress, or psychological reactions to stress, would benefit from further 32,33 Exploration of supports and strategies that enable successful quitting in the presence of these stressors is also indicated. Research on resilience to stress describes the pride associated with mastering the transition to becoming a non-smoker.…”
Section: Discussionmentioning
confidence: 99%
“…Contextual factors may help to explain these group differences. Although unemployment was common in both groups, Indigenous PWID may be more likely to experience systematic effects of labour market disadvantage, including family and community‐level impacts . In addition, while incarceration was common for both groups, Indigenous participants were more likely to have been incarcerated repeatedly, and approximately 40% of those who were had recently experienced dual drug dependence.…”
Section: Discussionmentioning
confidence: 98%
“…Psychological distress can be a consequence of social environmental stressors that are disruptive of self‐worth, efficacy and empowerment, and which may also lead to use of and dependence on injected drugs. Compared with non‐Indigenous Australians, Indigenous people have lower rates of educational attainment, higher unemployment, are overrepresented in juvenile detention and prison and are more likely to have experienced a range of traumatic events . Experiences of discrimination may be an additional source of social stress for Indigenous people .…”
Section: Introductionmentioning
confidence: 99%
“…T he health and wellbeing disparities between the Aboriginal and Torres Strait Islander people and other Australians are well documented 1–5 . Young Aboriginal people in particular suffer a disproportionately high burden of infectious diseases, 6 with respiratory, ear and skin infections being the most common reasons for children living in remote Aboriginal communities to present to clinics 7,8 …”
mentioning
confidence: 99%